2014
DOI: 10.3109/13697137.2014.915516
|View full text |Cite
|
Sign up to set email alerts
|

Hot flushes, hormone therapy and alternative treatments: 30 years of experience from Sweden

Abstract: Objectives The use of hormone therapy (HT) for hot flushes has changed dramatically over the past five decades.In this cross-sectional questionnaire study, the aim was to describe the use of HT and alternative treatments and to study the frequency of hot flushes. A further aim was to compare data from the present questionnaire with data from previous studies made in the same geographic area.Method A questionnaire was sent to a random sample of 2,000 women aged 47-56 years living in Östergötland County, Sweden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Past reports of hormone therapy use have not provided detailed information on the type of therapies used or on examined nonhormone or compounded therapies. 6,7,49 The main limitation of our study is that it required proficiency in written English. This did not significantly affect our results, as English literacy in Australian women exceeds 96%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past reports of hormone therapy use have not provided detailed information on the type of therapies used or on examined nonhormone or compounded therapies. 6,7,49 The main limitation of our study is that it required proficiency in written English. This did not significantly affect our results, as English literacy in Australian women exceeds 96%.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 After the publication of findings from the Women's Health Initiative, 5 the use of hormone therapy declined globally. 6,7 Conversely, compounded hormone therapies-which are promoted as natural but do not have established efficacy or safety-emerged. 8 Furthermore, androgen therapies are used by some women for female sexual dysfunction.…”
mentioning
confidence: 99%
“…In a Swedish study with data from 2010 [9], about 25% of perimenopausal and postmenopausal women reported severe VMS with a need for treatment. Menopausal hormone therapy (MHT) containing estrogen (combined with a progestogen for non-hysterectomized women) is the most effective treatment and reduces the frequency of VMS by at least 75% [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 17 18 19 ] In addition, 10% of women are prohibited from taking estrogen because of some diseases and hormone therapy is used in less than 20% of cases. [ 20 ] There is a growing concern among women about the use of these methods which is one of the reasons for women's lack of tendency for hormone therapy and their tendency to use nonpharmacological methods. [ 21 ] Over the past decade, the use of complementary and alternative medicine (CAM) to treat women's problems, including menopausal problems, has increased.…”
Section: Introductionmentioning
confidence: 99%